HYBRID CULTURAL IDENTITY IN EIICHIRO ODA’S ONE PIECE AND MATT OWENS’S ONE PIECE (2023) - Widodo, Alifia Nabila Putri; Marsih, Linusia (Proceeding of Conference on Literature, Linguistic, and Cultural Studies, 2025)
This study analyzes the construction and representation of hybrid identity in the narrative of One Piece (East Blue Arc) by Eiichiro Oda and its live-action adaptation by Matt Owens (2023). Drawing from Gérard Genette’s (1997) theory of intertextuality and Homi K. Bhabha’s (1994) concept of hybrid identity and third space, this study positions adaptation as a dialogic process that not only transfers stories across mediums, but also renegotiates values, cultural contexts, and identity representations. Through qualitative methods in the form of narrative analysis and visual discourse, this study also explores how these representations are reinforced in the live-action adaptation through the selection of multi-ethnic actors, global production design, and an emotional cinematic approach. The findings demonstrate that hybrid identity in One Piece is not only reflected in the text but is also widely recognized by global audiences as a reflection of universal values, such as freedom, solidarity, and resistance to hegemonic power. The tension between audience responses in the expectations of the original culture and the global approach carried out in the adaptation. Thus, this study emphasizes the importance of cross-media adaptation as a space for the formation of new, inclusive, and transformative cultural identities in the era of media globalization.